Mercy (politics) Luc Tuymans, Zlatko Kopljar - Desa'u, Ory ca. 20./21.Jh; Desa'u, Ory ca. 20./21.Jh (MER. Books, 2024)
Mercy (Politics) emerges from the collaborative exhibition between Luc Tuymans and Zlatko Kopljar, held at Galerija Vartai in Vilnius, Lithuania, in 2022. This compelling volume delves into the intersection of art and politics, showcasing the artists' profound engagement with political themes through their work. Featuring an extensive interview with each artist, the book provides insights into their creative processes, political views, and the conceptual underpinnings of their work. Edited by curator and writer Ory Dessau, Mercy (Politics) offers a deep exploration of art's role in addressing and reflecting upon contemporary political issues. The book is a testament to the power of artistic expression in navigating the complexities of modern society.
Ausstellungsdaten ermittelt
Keywords: Tuymans, Luc -- 1958-; Kopljar, Zlatko -- 1962-; Ausstellungskatalog -- Galerija Vartai -- 08.12.2022-27.01.2023 -- Vilnius